"Online Platform for Deep Learning Education" - Fourie, Aidan (African Institute of Financial Markets and Risk Management, 2020)
My thesis is going to focus on the development of a standalone, web based, machine learning educational platform. This platform will have a specific focus on neural networks. This tool will have the primary intention to provide a theoretical background to the mathematics of neural networks and thereafter to allow users to train their own networks on regression problems of their own creation. This is so as to provide the user with both theoretical, and first-hand, experience in the applications and functions of artificial intelligence. The primary success metric of this project will be how informative it is to the user. The key deliverable will be a fully functional prototype in additional to a written piece inclusive of a literature review and any other relevant findings and conclusions.